Peningkatan Hasil Belajar PAI Melalui Metode Card Sort di Kelas V UPTD SDN 03 Suayan - Imelda Sofia; Iswantir Iswantir; Defi Yuslia; Wirna Wirna; Desi Wirya; Alpinadri Alpinadri (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research was motivated by the low ability of children to read the Al-Quran in class V at UPTD SDN 03 Suayan. One solution to this problem is to implement activities using the Card Short method. This research aims to improve the Al-Quran reading ability of children in Class V UPTD SDN 03 Suayan. The method used in this research is the Classroom Action Research (PTK) method. This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings. Data collection techniques used were observation and documentation. The results of this study show an increase in children's scores from pre-action, cycle I and cycle II which can clearly be described as follows: the BB score at pre-action was 11 children or 55%, then in cycle 1 it became 5 children or 30%, then in cycle II it became 0 children or 0% MB value in pre-action 2 children or 10%, then in cycle 1 it becomes 2 children or 10% In cycle II it becomes 0 children or 0%, BSH value in the action there are 2 children or 10%, then in cycle 1 became 2 children or 10%, for cycle II 2 children 10%, the BSB value in pre-action was 5 children or 25% then in cycle 1 it became 5 children or 25% and in the end cycle II increased to 17 children or 85%. Based on the results of the research above, the researcher suggested to teachers to use the card short method as an alternative activity to improve children's ability to read the Al-Quran.